Physical and Mechanical Properties of Ni-Cr based composites with addition of solid lubricants produced through powder metallurgy process - Mohamad, W.F. (EDP Sciences, 2016)
Ni-Cr based composites with and without the addition of solid lubricants (MoS2, silver and CaF2) were prepared by powder metallurgy method. The samples were sintered at two different temperatures, 1000 °C and 1200 °C. The physical properties such as shrinkage, sintered density and porosity were studied. The microstructures of the Ni-Cr based composites were observed by using SEM analysis while the mechanical properties of the composites were measured by Rockwell Hardness Tester. The results revealed that the increased in sintering temperature improved the shrinkage, sintered density and hardness of the composites while less porosity produced. Ni-Cr based composites with the addition of silver and MoS2 exhibited better shrinkage, density and porosity. Besides, 5 of MoS2 addition in the composites improves the hardness of the composites at sintering temperature 1200°C. © The Authors, published by EDP Sciences, 2017.